Implementation of Coding-Based Learning as a Digital Learning Culture in Grade V at SD Negeri Ambulu II, Probolinggo Regency - Nur Rahmat; Faridahtul Jannah; Shofia Hattarina; Ribut Prastiwi Sriwijayanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the implementation of coding learning as part of a digital learning culture in Grade V at SD Negeri Ambulu II, Probolinggo Regency. The study focuses on the planning, implementation, assessment system, interaction patterns between teachers, students, and technology, as well as the challenges encountered during implementation. A qualitative approach with a descriptive research design was employed. Data were collected through observations, interviews, and documentation involving the principal, Grade V teacher, and students. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that coding learning was implemented systematically through integrated planning, implementation, and assessment supported by digital technology. Teachers utilized digital learning media and project-based learning to enhance students’ creativity, critical thinking, collaboration, and digital literacy. Coding learning also fostered more active, communicative, and collaborative interactions between teachers and students, contributing to the development of a digital learning culture within the school. Furthermore, it promoted students’ independent learning, creativity, problem-solving abilities, and adaptability to technological advancements. However, several challenges remained, including limited technological facilities, teachers’ readiness to manage digital learning, and differences in students’ abilities to understand coding concepts. Overall, coding learning represents an innovative instructional strategy that supports the strengthening of digital learning culture and the development of essential twenty-first-century competencies in elementary school students.